Whistleblowers : incentives, disincentives, and protection strategies - Lipman, Frederick D. (Hoboken, N.J. : Wiley, 2012)
"The book will discuss business protection strategies and best practices in dealing with whistleblowers, as well as the GlaxoSmithKline, Pfizer and other high profile whistleblower cases. The book is expected to appeal to Board members, C-Suite executives, corporate compliance personnel, attorneys for whistleblowers and defense attorneys as well as all potential employee whistleblowers. The book emphasizes the disincentives to whistleblowing, and will review the academic studies of whistleblowers with the idea of developing best practices to deal with whistleblowers: Introduction. 1. Dodd-Frank Incentives to Whistleblowers 2. The Remarkable Story of Cheryl Eckard and the $96 Million Bounty 3.The Pfizer Over $100 Million Bounty Collectors 4.Other Statutory Incentives to Whistleblowing 5.Disincentives to Whistleblowers and Academic Studies of Whistleblowers 6.Best Practices in Complying with the U. S. Department of Justice Guidelines 7.Best Practices for CEOs in Dealing with Whistleblowers 8.Best Practices for Conducting Whistleblower Investigations 9.The New SEC Whistleblower Rules 10.Qui Tam Actions and Their Defense "--
Includes bibliographical references and index.
Keywords: Whistle blowing -- United States; Business ethics -- United States; Whistle blowing -- Law and legislation -- United States; Whistle blowing -- Case studies